Morphomechanics of development - Beloussov, Lev V. (Springer International Publishing : Imprint: Springer, 2015)
This book outlines a unified theory of embryonic development, assuming morphogenesis to be a multi-level process including self-organizing steps while also obeying general laws. It is shown how molecular mechanisms generate mechanical forces, which in the long run lead to morphological changes. Questions such as how stress-mediated feedback acts at the cellular and supra-cellular levels and how executive and regulatory mechanisms are mutually dependent are addressed, while aspects of collective cell behavior and the morphogenesis of plants are also discussed. The morphomechanical approach employed in the book is based on the general principles of self-organization theory.